Population parameters of two common mantis shrimps species of Pantai Remis coastal waters - Mohd Taher, Nur Ain Sofea (2012)
The study is an effort to estimate the length-weight relationship, sex ratio and population parameters of two common mantis shrimps collected from the coastal waters of Pantai Remis, Perak between February 2012 and October 2012 using trawl nets. The two common mantis shrimps collected are Harpiosquilla harpax and Miyakea nepa. A total length and weight of 804 specimens of H. harpax and 695 specimens of M. nepa were measured and the sex ratio for H. harpax is 1:0.83 (males: females) while for M. nepa, the sex ratio is 1:1.46 (males: females). Males of H. harpax were predominant than the females and females were predominant for M. nepa throughout the study period. For the length-weight relationship, both species exhibit negative allometric for males, females and combined sexes as their value is below 3. The value of b for H. harpax were 2.698 for males and 2.884 for females while for M. nepa the value of b were 2.480 for males and 2.481 for females. For combined sexes of both species, value of b was 2.852 for H. harpax and 2.412 for M. nepa. FiSAT II software package was used to estimate the growth and mortality parameters such as asymptotic length (L∞), growth coefficient (K), total mortality (Z) and natural mortality (M), exploitation rate (E) and recruitment pattern. The L∞ and K for H. harpax were 18.38 cm and 1.10 yˉˡ for males and 21.53 cm and 0.75 yˉˡ for females while for M. nepa, the L∞ and K were found to be 16.28 cm and 1.10 yˉˡ for males and 17.73 cm and 0.75 yˉˡ for females. The growth performance index (φ') for H. harpax was 2.57 for males and 2.541 for females while for M. nepa, the growth performance index (φ') was 2.465 for males and 2.372 for females. Total mortality (Z), natural mortality and fishing mortality for H. harpax was 4.084 yˉˡ for males and 3.259yˉˡ for females, 2.247 yˉˡ for males and 1.674 yˉˡ for females, 1.837 yˉˡ for males and 1.585 yˉˡ for females respectively. Total mortality (Z), natural mortality and fishing mortality for M. nepa was 3.648 yˉˡ for males and 3.248 yˉˡ for females, 2.325 yˉˡ for males and 1.767 yˉˡ for females, 1.323 yˉˡ for males and 1.481 yˉˡ for females respectively. The recruitment patterns of both species were continuous throughout the year. The exploitation rate (E) for H. harpax were 0.499 for males and 0.486 for females while for M. nepa, the rate of exploitation (E) were 0.363 for males and 0.456 for females.